Rapid Atlantification along the Fram Strait at the beginning of the 20th century - Tesi, Tommaso; Muschitiello, Francesco; Mollenhauer, Gesine; Miserocchi, Stefano; Langone, Leonardo; Ceccarelli, Chiara; Panieri, Giuliana; Chiggiato, Jacopo; Nogarotto, Alessio; Hefter, Jens; Ingrosso, Gianmarco; Giglio, Federico; et al. (Science Advances, 2021)
The recent expansion of Atlantic waters into the Arctic Ocean represents undisputable evidence of the rapid changes occurring in this region. Understanding the past variability of this “Atlantification” is thus crucial in providing a longer perspective on the modern Arctic changes. Here, we reconstruct the history of Atlantification along the eastern Fram Strait during the past 800 years using precisely dated paleoceanographic records based on organic biomarkers and benthic foraminiferal data. Our results show rapid changes in water mass properties that com-menced in the early 20th century—several decades before the documented Atlantification by instrumental records. Comparison with regional records suggests a poleward expansion of subtropical waters since the end of the Little Ice Age in response to a rapid hydrographic reorganization in the North Atlantic. Understanding of this mechanism will require further investigations using climate model simulations.INTRODUCTIONClimate reconstructions of the Common Era are fundamental bench-marks to place human-induced changes into the context of natural climatic change (1, 2). This is particularly relevant for the Arctic, which is currently warming faster than any other region (3). Arctic warming has been associated with rapid sea ice decline and expan-sion of Atlantic waters (AWs) into the Arctic basin (4, 5) — a phenomenon commonly referred to as “Atlantification” (6). While in situ observations and satellite images provide high-resolution records of anomalies in water mass properties and sea ice since the 1930s and 1980s (4, 7–10), respectively, little is known about this phenomenon in pre- and early-industrial times. Because natural archives preserve evidence of past climate variability, they can offer a longer-term perspective on Atlantification in this region.The Fram Strait represents an important oceanographic gateway that allows the exchange of Arctic and AW masses (11). Low-resolution paleoceanographic records suggest that the summer temperatures of the AW ...